Analysis of mouse intestinal organoid culture with conditioned media isolated from mucosal enteric glial cells - Meryem B. Baghdadi; Tae-Hee Kim (STAR Protocols, 2022)
Summary: This protocol describes the isolation and culture of 3D intestinal crypt organoids with stromal niche cells. We show a murine organoid culture system that utilizes conditioned media isolated from primary, mucosal enteric glial cell culture. We describe three assays of analyzing this organoid culture: flow cytometry, gene expression, and organoid morphology analyses. This protocol can also be used to study the mechanisms of stem cell interaction with other stromal niche cell types such as mesenchymal cells and innate immune cells.For complete details on the use and execution of this protocol, please refer to Baghdadi et al. (2021).